Prompt Response to single injection of Bevacizumab in a case of Fibrinous Central Serous Choroidopathy (CSC). (Bangladesh Journal of Medical Science, 2017)
Purpose: Central Serous Choroidopathy (CSC) is a disease of young and middle aged adults as a localized detachment of the neurosensory retina. Though the cause of CSC remains unknown, it is believed that abnormalities in choroidal circulation make overlying retinal pigment epithelium dysfunctional, resulting in development of a serous retinal detachment. Subretinal fibrin accumulation is rare but vision threatening association of CSC.Methods: A young 31 years female with acute central serous chorioretinopathy received an Intravitreal bevacizumab (1.25 mg/0.05 ml) injection. At baseline and follow-up visits, patients had best corrected visual acuity (BCVA), IOP assessment, dilated fundus examination, fundus photography, fluorescein angiography (FA), and Optical Coherence Topography(OCT) imaging.Results: Patient showed resolution of fibrin, resolution of intraretinal or subretinal fluid promptly, and improvement in visual symptoms and acuity within 1 month. At 6 months patient is maintaining 20/20 vision without any recurrence.Conclusions: Intravitreal bevacizumab injection for acute fibrinous central serous choroidopathy may result in prompt resolution of neurosensory detachment and reduction of angiographic leakage. These short-term results suggest that Intravitreal bevacizumab injection may constitute a promising therapeutic option in fibrinous central serous chorioretinopathy.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.157-160